THE ANALYSIS OF A NUMBER OF PROPERTIES OF H12MF STEEL AFTER HIGH-ENERGY PROCESSING - V. A. Kalinichenko; M. L. Kalinichenko; M. A. Kardapolova; P. N. Veremey (Литьë и металлургия)
Laser processing allows to concentrate high level of energy on material surface and the increase of surface hardness can be reached by receiving of uniform fi e-grained structure with impurities of the carbide-containing phases uniformly distributed in matrix. Analysis of properties of H12MF steel after processing by various laser machines was carried out and a number of measures for use of this technology are recommended in the present article.